The pilot study of SMART-Resilience a psycho-educational program - Kadek Suranata (Indonesian Counselor Association (IKI), 2019)
This pilot study is aimed at evaluating the feasibility of the Smart resilience program for secondary school students. The one group pretest and posttest experiment design conducted by involved 45 of second grades students of secondary school in Province of Bali, Indonesia as a participant. In each are of urban, suburb and rural schools consist of 15 students. The Indonesian version of students well being scale used to collect the data for pretest and post test assessment. Repeated Measure ANOVA conducted on the analysis of the data through the JASP program. The results of this study indicate; (1) Smart-Resilience programs are effective to improve student well-being in overall school areas, (2) there are differences in the effectiveness for students in urban, suburb and rural school areas, (3) the programs achieve a high acceptance and accessibility by students and the school counselor